(3WHjYI GdeSFhdjI GdLfGFjI ai GdLQGFe GdeGOjI (B: s (3OQGSI ebGQfI Hjf GdfXGe GddGJjfi hGdGfLdhScShfi hGdTQjYI GdESdGejI (B/ s - (3haGA Qhajb s; (3GMeO YhV HdGd (B: s ((3haGA Qhajb (B: s, 2009)
(3JHYG ddOQGSI GdJi CLQGgG GdHGMK JhUd Edi Cf GdeSFhdjI GdLfGFjI Yf GdLQGFe GdeGOjI JJMbb HYjOG Yf GdHMK ai eOi JhGaQ GdQcf GdeYfhi HCi ef UhQJjI EP JcJai HeLQO GdEQJcGH Ch GdEeJfGY hYdi GdQZe ef SjGOI GdbGYOI GdJi JbVi HCf(B"(3dG LQjeI HOhf NWC(B"(3EdG Cf GdJTQjYGJ GdebGQfI dGRGdJ eNdUI dgPG GdfhY GdHOGFi ef GdeSFhdjI EP MGaXJ Ydi MjR dgG ai fWGb bGfhf GdYbhHGJ hcPG GdbhGfjf GdNGUI hPdc EYeGdG ddaYGdjI hSQYI GdHJ ai GdbVGjGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2009s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeSFhdjI GdLfGFjIs; (3GdeSFhdjI GdehVhYjI s; (3GdeSFhdjI HOhf NWC s; (3QSGFd LGeYjIs